The efficacy of Topical Clascoterone versus systematic spironolactone for treatment of acne vulgaris: A systematic review and network meta-analysis. - Mohammad A Basendwh; Amer Abdulaziz Alharbi; Sarah Abdulla Bukhamsin; Rahaf Abdulrashid Abdulwahab; Sarah Abdullah Alaboud (PLoS ONE)
Objectives This study aimed to evaluate the effectiveness of topical clascoterone (TC) compared to oral spironolactone for acne vulgaris treatment. Methods A computerized search through PubMed/MEDLINE, SCOPUS, and the Cochrane Library was conducted to find relevant papers. We used the "netmeta" and "meta" packages for network meta-analysis (NMA) in RStudio 1.2.5019 (2009-2019 RStudio, Inc.) to conduct all of our statistical tests. Results Seven articles (n = 2,006 patients) were included. The fixed-effect size showed that TC 1% bis in die (BID) showed potential effectiveness in reducing the inflammatory and non-inflammatory lesion count compared to placebo (Standardized mean difference, SMD = -0.27, 95% CI: -0.36 to -0.17) and (SMD = -0.31, 95% CI: -0.41 to -0.22), respectively. The random-effect size showed that TC 1% BID was significantly associated with a 12-week treatment success compared to placebo (Odds ratio, OR = 2.44, 95% CI: 1.12 to 5.30). Spironolactone 200 mg was associated with a significant reduction in total lesion count (SMD = -4.46, 95% CI: -5.60 to -3.32). Conclusion TC appears to reduce both inflammatory and non-inflammatory lesion count and may lead to treatment success. Spironolactone at 200 mg showed potential effectiveness in terms of total lesion count reduction. These results suggest that both TC and Spironolactone could be beneficial in treating patients with acne vulgaris.